TINJAUAN YURIDIS PERLINDUNGAN HUKUM PELAKU USAHA YANG MENGALAMI KERUGIAN DARI ITIKAD TIDAK BAIK KONSUMEN - TINJAUAN YURIDIS PERLINDUNGAN HUKUM PELAKU USAHA YANG MENGALAMI KERUGIAN DARI ITIKAD TIDAK BAIK KONSUMEN (Kerta Dyatmika, 2022)
Law Number 8 of 1999 concerning Consumer Protection regulates consumer obligations in Article 5 letter b, namely that violators have good intentions in carrying out the business of purchasing goods. Currently, losses are often experienced by business actors due to failure to fulfill the achievements that consumers should have made, which causes losses to business actors, including bringing food from outside where business actors have informed potential consumers that the products being sold are halal products but there is still consumer bad faith that causes losses to business actors.The type of research used in this research is normative legal research which is a scientific research procedure to find the truth based on scientific logic from a normative side. Using a legislative approach with primary legal materials, secondary legal materials and tertiary legal materials.The conclusion of this research is that there is legal protection for business actors. Legal protection is an action that protects and/or provides assistance to sufferers whose rights have been taken away or harmed. Business actors prioritize consumer rights, namely selling goods and/or services that are quality and safe when used. Consumer satisfaction is also measured from the responsibilities of business actors as explained in Law Number 8 of 1999 concerning Consumer Protection.